Formulation Cream of Ethanol Patikan Kebo Weeds (Euphorbia hirta L.) Extract As An In Vitro Anti-Acne - Lydia Br Barus; Sanna Kamisna Royani Purba; Sesilia Sri Susandri Br. Gultom; Helen Anjelina Simanjuntak; Hermawan Purba; Nurbaiti Br. Singarimbun; Defacto Firmawati Zega (Universitas Labuhanbatu, 2025)
Background: Acne is a skin inflammation that is prevalent in 80-100% of the population, particularly during adolescence. The Patikan Kebo (Euphorbia hirta L.) weed plant is employed in a cream formulation to treat acne. Therefore, this study aims to determine the formula of the Patikan Kebo (E. hirta L.) weed cream preparation that is as effective as an in vitro anti-acne. Methodology: the research method was carried out experimentally with the stages of sample preparation, phytochemical screening, extraction, formulation, evaluation, and antibacterial activity test that caused acne using the well diffusion method. Findings: The results showed the Patikan Kebo (E. hirta L.) weed has secondary metabolites consisting of alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids. The evaluation of the cream preparation of each formula has met cosmetic standards. The diameter of the F4 inhibition zone has antibacterial activity against acne-causing Propionibacterium acnes (12.03 ± 0.81 mm), Staphylococcus epidermidis (11.48 ± 1.10 mm), S. aureus (12.07 ± 0.06 mm), and the F5 inhibition zone P. acnes (13.53 ± 0.15 mm), S. epidermidis (12.54 ± 0.75 mm), and S. aureus (13.03 ± 0.61 mm). Formulas F4 and F5 are more effective as anti-acne with a strong inhibition zone diameter. Contribution: These findings indicate that formulas F4 and F5 can be further developed as alternative natural active ingredients in cosmetic or pharmaceutical products for acne therapy, thus contributing to the development of safer, more economical, and more sustainable local herbal medicine